Characterization of anti-theft devices directly from the surface of banknotes via easy ambient sonic spray ionization mass spectrometry. Issue 5 (September 2015) - Schmidt, Eduardo Morgado; Franco, Marcos Fernando; Cuelbas, Claudio José; Zacca, Jorge Jardim; de Carvalho Rocha, Werickson Fortunato; Borges, Rodrigo; de Souza, Wanderley; Sawaya, Alexandra Christine Helena Frankland; Eberlin, Marcos Nogueira; Correa, Deleon Nascimento
Abstract: Using Brazilian banknotes as a test case, forensic examination and identification of Rhodamine B dye anti-theft device (ATD) staining on banknotes were performed. Easy ambient sonic spray ionization mass spectrometry (EASI–MS) was used since it allows fast and simple analysis with no sample preparation providing molecular screening of the surface with direct desorption and ionization of the security dye. For a more accurate molecular characterization of the ATD dye, Q Exactive Orbitrap™ Fourier transform (tandem) mass spectrometry using eletrospray ionization (ESI–HRMS/MS) was also applied. Graphical abstract: Highlights: ATM thefts, particularly with the use of explosives, are a serious and increasing crime in Brazil. Rhodamine B dye was applied as anti-theft security ink in Brazil. EASI–MS for the rapid screening and spatial analysis of Rhodamine B on banknotes from ATM thefts EASI–MS provide no step preparation and no crime evidence destruction, essential in forensic research. Q Exactive Orbitrap™ Fourier transform mass spectrometry as powerful tool to confirmation analysis